Is high flow nasal cannula as an effective oxygen delivery alternative in intensive care unit? - Patel, Amrish; Atram, Jitesh; Dumra, H. S.; Dandnaik, Mansi; Raval, Gopal (International Journal of Advances in Medicine, 2019)
Background: High-flow nasal cannula (HFNC) oxygen therapy is carried out using an air/oxygen blender, active humidifier, single heated tube, and nasal cannula. It is an oxygen delivery system which uses air blender to deliver accurate oxygen concentration to the patient from 21% to 100% at desired temperature. It can be administered via wide bore nasal cannula or to the tracheostomy tube via connector. It can give upto 60L/min flow hence can generate positive end expiratory pressure between 2 to 7 cmH20. By providing humidified oxygen along with the high flow rates it satisfies air hunger and reduces work of breathing for the patient. Methods: This is a retrospective observational study. Patients with persistent hypoxia in spite of conventional oxygen therapy were treated with HFNC. Patients with possible need for immediate invasive ventilator support were excluded. Clinical respiratory parameters and oxygenation were compared under conventional and HFNC oxygen therapy. Results: Thirty patients, aged more than 18 years admitted in intensive respiratory care unit with acute hypoxemic respiratory failure from June 2017 to January 2018 were included in the study. Study period was of 6 months. Etiology of acute respiratory failure (ARF) was mainly pneumonia (n = 17), interstitial lung disease (n = 5), bronchial asthma (n=3) and others (n = 5). There was statistically significant reduction in respiratory rate (29.40 before Vs 23.50 after; P- <0.0001) and significant improvement in comfort level of the patient after HFNC therapy. Median duration of HFNC was 48 hrs (24-360) hours. Five patients were intubated later on and 4 died in the intensive care unit. Conclusions: Use of HFNC in patients with persistent ARF was associated with significant and sustained improvement of clinical parameters (respiratory rate). It can be used comfortably for prolonged periods.